IMPLIKASI FILSAFAT ILMU TERHADAP PERKEMBANGAN ILMU PENGETAHUAN DAN TEKNOLOGI - Fitriani, Yustia Racham; Andita Dwi Puspitaningsih; Ari Abi Aufa (As-Sulthan Journal of Education, 2025)
The development of science and technology is inseparable from the fundamental role of the philosophy of science as its conceptual and methodological foundation. Through its three main dimensions, ontology, epistemology, and axiology, the philosophy of science provides direction in determining the objects of scientific inquiry, the methods for obtaining valid knowledge, and the ethical values guiding the application of technology. Ontologically, it defines the nature and boundaries of the reality being studied, thereby encouraging the emergence of new scientific disciplines. Epistemologically, it shapes the framework of systematic and critical scientific methods that underpin modern technological advancements based on empirical research. Axiologically, it ensures that the use of technology remains ethical, responsible, and oriented toward human welfare. Thus, the philosophy of science not only establishes the theoretical foundation for the progress of science and technology, but also ensures that such advancement proceeds in a responsible and sustainable manner.